Sistem Informasi Keuangan Bidang Pengadaan Bahan Material Berbasis Website (Studi Kasus CV Ridho Jaya Brother) - Nabila Kaulan Karimah; Eka Puji Agustini (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
CV Ridho Jaya Brother is engaged in the procurement of materials, performs its financial activities manually, is recorded in a ledger which is limited to recording income and expenses without using an account so that it does not have financial reports based on actual accounting. This causes financial activities to be vulnerable to cases of theft of funds, inaccurate financial reports, not on time, so that the results cannot be compared from year to year to see an increase or decrease in profit. The research objective is to design a financial information system that is integrated with financial data, in the form of a financial information system website in the field of Material Procurement at CV Ridho Jaya Brother. The system development method uses the waterfall method starting from communication, planning, modeling, construction, and deployment.. The results of the design of the financial website program code are implemented using HTML, PHP, Javascript, and CSS. The results of the financial system products on CV Ridho Jaya Broter were very helpful and facilitate their financial activities, where financial managers can easily record transactions, have broad access so that they can be done anywhere, financial reports are accurate, timely and quickly obtained, and make financial reports as a source of information. basis for future decisions